Effects of Functional Oligosaccharides Extracted from Straw on the Growth, Feeding, Physiology, Histology, Muscle Texture, and Gut Microbiota of Micropterus salmoides - Benli Wu; Long Huang; Cangcang Wu; Jing Chen; Xiajun Chen; Xiang Wang; Kai Cui; Zhigang Liu; Jixiang He (Aquaculture Nutrition)
We conducted an 8-week feeding trial to investigate the effect of mixed functional oligosaccharides (chitosan oligosaccharide, fructooligosaccharide, and xylooligosaccharide) extracted from wheat straw on the growth, feeding, physiology, histology, muscle texture, and gut microbiota of Micropterus salmoides. Six diets were formulated by incrementally adding mixed functional oligosaccharides (0.1, 0.5, 1.0, 1.5, and 2.0 mg/kg) to the control diet. 30 individuals with initial body weight of 25.1±3.5 g were randomly allocated to 6 triplicate tanks and fed to apparent satiation twice daily. The fish fed 1.0 mg/kg additives displayed maximum growth, and the feed conversion ratio decreased with the increase in additives from 0 to 1.0 mg/kg (P<0.05) but did not decline further with the addition of more than 1.0 mg/kg (P>0.05). The villus height and width were significantly higher in the supplementation groups than in the control group, while the gut and liver structures presented abnormalities with excessive supplementation above 1.5 mg/kg. There were significant differences in muscle texture indices for M. salmoides over the fed additive gradient, and the hardness, gumminess, and chewiness were highest in the 1.0 mg/kg group. High oligosaccharide levels, such as 2.0 mg/kg, decreased the LZM level, while there were no significant differences in the SOD and MDA levels. Gut microbiome analysis revealed no significant differences in richness and diversity for groups fed the functional oligosaccharide gradient; however, the PCoA results showed that the microbial community composition changed markedly in response to different addition levels, and the 0.5 and 1.0 mg/kg supplementation groups were far apart from the lower and higher supplementation groups. The relative abundance of Proteobacteria was lower in the 0.5 and 1.0 mg/kg addition groups, while that of the phyla Fusobacteria and Firmicutes were higher in these two groups. Functional classification showed that microbes related to carbohydrate metabolism were more abundant in the 0.5 and 1.5 mg/kg groups than in the other groups.